SUPERVISI VIRTUAL PROGRAM PENGENDALIAN TUBERKULOSIS PARU ERA PANDEMI COVID-19 DI KABUPATEN OKU TIMUR - Siti Patria Hutami; Yodi Mahendrahata; Diah Ayu Puspandari (Journal of Health Service Management, 2021)
Background: COVID-19 requires all parties to adapt to an unprecedented situation. Meanwhile, the implementation of the Pulmonary TB Control Program activities must continue to support the success of the Pulmonary TB Control Program in East OKU Regency. Coaching which is usually done face-to-face but is now very difficult to do because the COVID-19 has not subsided. Modern technology that reaches all aspects of life, including supervision activities. Objective: To describe the virtual supervision mechanism carried out by the Regional Health Department to the primary health care during the Covid-19 pandemic in the Pulmonary TB Control Program in East OKU Regency. Methods: A descriptive case study approach through a single case holistic design. Qualitative information was obtained through in depth interviews and documentation studies on April-Mei 2021. The research subjects were taken by the purposive sampling method. The subjects were 16 people. Results: The implementation of virtual-based supervision activities was carried out via WhatsApp and telephone from the Regional Health Department to the primary healthcare. Virtual supervision made it easier to access communication between the Health District Office and the TB Program Manager at the puskesmas because there are no restrictions on funds, distance and time. The Health District Office were able to monitor MSS achievements through the SITB report and monitor the availability of drug stocks virtually through coordination with the TB Program Manager at the puskesmas. However, the Health District Office was unable to monitor the use of logistics and reports related to slide numbering at the puskesmas in addition to the limited guidance provided during the COVID-19 pandemic. Conclusion: Social media is used as a means of exchanging data and information. Virtual monitoring of activities and coaching has not been carried out optimally. Coaching needs to be done virtually to improve the ability and skills of a TB Programmer in terms of recording and reporting TB programs during the pandemic of COVID-19.